Nivel de conocimiento de la madre sobre lactancia materna exclusiva y su relación con la glicemia neonatal - Salazar Chero, María Elena (2017)
This research descriptive, transverse and correlational court, was conducted during the months of July and August 2015 on the premises of Leoncio Prado Hospital of Huamachuco province Sánchez Carrión, in order to determine S. The Relationship Between Knowledge Mother Breastfeeding Exclusive and neonatal glycemia. The sample universe consisted of 30 mothers of term infants Unit Maternity Hospital Leoncio Prado Huamachuco, taking into account the criteria for inclusion. Data collection was obtained by the application of instruments: Knowledge of Mother Breastfeeding and neonatal glycemia control. Were Tabulated data obtained and presented in the Statistical Tables of single and double entry. Statistical Analysis for the test of independence of criteria (x2) was applied. After analysis they were reached the following conclusions: The level of knowledge of the mother on exclusive breastfeeding was good in 70%, normal is 24% and 6%. The relationship between the level of knowledge of the mother and the glycemia of the neonate at 2 hours of life (P: 0.007 highly significant relationship) and 6 hours of life (P: 0.049 significant relationship) was determined, with no relation between the level Knowledge of the mother and the glycemia of the neonate at birth.